Tanda Tangan Elektronik sebagai Solusi Hukum Perikatan dalam Era Digital di Indonesia - Devi Chintya Dewi; Dinda Amelia; Faizal Rakha Pratama; Faturachman Shidiq; Firgy Ferdansyah (Letterlijk, 2024)
In the rapidly developing digital era, technology has made various aspects of life easier, including electronic signatures (TTE).  This research examines the validity of TTE from the perspective of civil law, the Information and Electronic Transactions Law (UU ITE), as well as the certification process and the risks of using uncertified electronic signatures.  The purpose of this research is to understand the legal strength and security of TTE, and the stages that must be passed to obtain a certified electronic certificate and what the risks are of using an uncertified electronic signature.  This research uses a juridical-normative method with data collection techniques through literature studies from literature, laws and scientific articles.  The research results show that TTE has legal force equivalent to a wet signature if it meets certain requirements, such as authentication of the owner of the signature and document.  In addition, verification and certification by an Electronic Certification Organizer (PSrE) recognized by the Ministry of Communication and Information (Kominfo) is an important step to ensure the validity and security of TTE.  This research also highlights the risks of using uncertified TTE, which can reduce the security and validity of documents.  Thus, the use of certified TTE is crucial to support safe and legally valid digital transactions.